The Spiritualization of Secular Society: The Challenge of Peace in a World of Diversity. (November 2019) - Helminiak, Daniel A.
Peace on earth is not to be expected. First, at least in its subhuman form, the law of nature is survival of the fittest, not self-deferential cooperation. Second, a philosophical consensus to provide needed epistemological agreement and ethical criteria for peace is nonexistent in the postmodern world. Third, conflicting beliefs among the world's religions and a sharp decline in religious affiliation incapacitate the traditional agencies of support for transcendent values, including peace. Thus, the daunting challenge has become the nonreligious and even nontheological spiritualization of secular society. Only this hope remains as history forces humanity to mature: Elaborate and rely on a humanistic basis for lofty values. In evocative terms, philosophers and humanistic psychologists have narrated that hope. More incisively, Bernard Lonergan has detailed the humanistic basis of that hope: distinctively human consciousness or spirit, the self-transcending dimension of the human mind, a bimodal, quadrilevel, epistemologically and ethically normative dynamism. But no agency exists to implement this hope, and peace still, depends ultimately on elusive human goodwill. Still the empirical specification of a philosophical foundation at least provides needed guidance, which, coupled with today's scientific, medical, psychological, and sociological technology, does sustain hope for peace.